2023
DOI: 10.1002/prs.12439
|View full text |Cite
|
Sign up to set email alerts
|

Workplace accident analysis in the Algerian oil and gas industry

Abstract: A total of 42,032 workplace accidents were reported in 2021 by the Algerian National Social Insurance Fund for Salaried Workers in Algeria, of which 38,225 were accidents within the workplace and 3807 were related to traffic accidents or other reasons. Most of these accidents were recorded in the building and construction field, followed by the oil and gas company exploration and drilling, which comes at the forefront of the Sonatrach company. This study aims to analyze accidents in the workplace using quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the same sense, it has been confirmed that the social factor, through the workforce and product responsibility mainly, positively influences financial performance in the O&G sector. It can be seen how issues related to a safe and healthy workplace or a product and service where consumer safety is integrated are relevant issues for a sector such as the O&G where its working practices and production processes can sometimes have devastating consequences for the worker or the consumer (Zerrouki, et al 2023). A optimal health and safety policy in the workplace and during the production process will allow the sector not only to benefit from a reduction of possible unintentional accidents, but will also allow it to increase stock value, as the results obtained corroborate.…”
Section: Discussionmentioning
confidence: 99%
“…In the same sense, it has been confirmed that the social factor, through the workforce and product responsibility mainly, positively influences financial performance in the O&G sector. It can be seen how issues related to a safe and healthy workplace or a product and service where consumer safety is integrated are relevant issues for a sector such as the O&G where its working practices and production processes can sometimes have devastating consequences for the worker or the consumer (Zerrouki, et al 2023). A optimal health and safety policy in the workplace and during the production process will allow the sector not only to benefit from a reduction of possible unintentional accidents, but will also allow it to increase stock value, as the results obtained corroborate.…”
Section: Discussionmentioning
confidence: 99%